The Concept of the Power and Asymmetry of Power in Business Relationships: A Systematic and Bibliometric View of the Literature - Klaudia BRACIO (Communications of International Proceedings, 2021)
The purpose of this article is the identification areas of scientific research in which the topic of power in business-to-business relations is addressed based on the systematic review and on the analysis of bibliometric data of scientific publications. The literature on the subject shows that power and power asymmetry are commonly regarded as inherent features of the mutual relations between sellers and buyers. Regardless of the growing number of studies related to the asymmetry of power in business relationship here is still a lack of research that integrates and synthesizes this body of knowledge. Knowledge about relationships is relatively one-sided as researchers focus on the positive aspects of relationships. However, many authors emphasize that in the business reality not all lasting relationships are based on positive feelings and the good will of partners. In terms of research methods, a systematic and bibliometric view of the literature, based on the 135 publications located in reputable scientific databases (Scopus and Web of Science) between the years 1991–2021 and Rapid Automatic Keyword Extraction (RAKE), was applied. The selection of the articles for further analysis is perceived as the main limitation of this study, as some papers may not have been included due to missing keywords or due to having been absent from the two selected databases. The article analyses theoretical research and empirical papers and enables identification of problems in the current research as well as identifying trends in the area of the studied phenomenon. The proposed research fills the gap concerning a review of literature on this topic and provides an analysis of 30 years of scholarly research, highlighting the concept of the asymmetry of power in business relationship.
Keywords: Power Asymmetry; Business-To-Business Relations; Power; Systematic Literature Review.